2022
DOI: 10.1007/s44192-022-00019-w
|View full text |Cite
|
Sign up to set email alerts
|

Child, adolescent, and parent mental health in general population during a year of COVID-19 pandemic in belgium: a cross-sectional study

Abstract: Background This study aims to evaluate the mental health status of children, adolescents and their parents during the first year of COVID-19 pandemic in Belgium. Method Analysis compared results before and during the second national lockdown, which started on November 2nd 2020. A cross-sectional online survey was conducted between May 2020 and April 2021. Results Two hundred and eighteen adults and 273… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
2
Order By: Relevance
“…When compared to surveys conducted among parents at the global level, our generalized anxiety prevalence was lower than that found in France during the first lockdown (51.4%) [10] but slightly higher than that of Belgium (40.7%) [11]. However, our depression prevalence was much lower than those found in Belgium (54.6%) [11] and South Korea (46.5%) when combining mild and moderate to severe depression [14].…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…When compared to surveys conducted among parents at the global level, our generalized anxiety prevalence was lower than that found in France during the first lockdown (51.4%) [10] but slightly higher than that of Belgium (40.7%) [11]. However, our depression prevalence was much lower than those found in Belgium (54.6%) [11] and South Korea (46.5%) when combining mild and moderate to severe depression [14].…”
Section: Discussioncontrasting
confidence: 76%
“…When compared to surveys conducted among parents at the global level, our generalized anxiety prevalence was lower than that found in France during the first lockdown (51.4%) [10] but slightly higher than that of Belgium (40.7%) [11]. However, our depression prevalence was much lower than those found in Belgium (54.6%) [11] and South Korea (46.5%) when combining mild and moderate to severe depression [14]. Both generalized anxiety and depression levels found in this study are higher than those found in a two-wave survey in Norway (depression of 23.0%, generalized anxiety of 23.3% in the 1st wave, and depression of 16.8% and generalized anxiety of 13.8% in the 2nd wave) [12].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Moreover, the mental health of children and young people within urban settings has increasingly come to the forefront during the COVID-19 pandemic. Evidence suggests that the pandemic, as well as isolation and loneliness as a consequence of lockdown measures, have led to a considerable increase in symptoms of depression and anxiety in young people [ 9 , 10 ]. Even post the COVID-19 pandemic, the rates of psychological symptoms seem to remain remarkably high.…”
Section: Introductionmentioning
confidence: 99%